Digital Health in Kidney Care: The Role of Telemonitoring in Enhancing Self-Management Among Patients with Chronic Kidney Disease - Silalahi, Martha Katarina (Oshada, 2025)
Chronic kidney disease (CKD) requires long-term, continuous self-management to prevent disease progression and reduce complications. However, maintaining patient adherence and engagement in daily self-care remains a major challenge. The rapid development of digital health, particularly telemonitoring, offers new opportunities to strengthen self-management by enabling continuous home-based monitoring, real-time feedback, and enhanced patient–provider communication. This study aims to analyze the role of telemonitoring in improving self-management among patients with CKD and to identify the system design and adherence-related factors that determine successful implementation. A systematic literature review was conducted following the PRISMA framework, using articles published between 2020 and 2025 retrieved from Scopus, PubMed, Web of Science, and Google Scholar. The findings indicate that telemonitoring significantly improves key dimensions of self-management, including self-efficacy, treatment adherence, symptom awareness, patient engagement, and satisfaction with care. Clinical benefits include improved blood pressure control and enhanced early detection of complications. Nevertheless, long-term adherence remains a critical barrier, strongly influenced by system usability, monitoring burden, digital literacy, and integration within clinical workflows. In conclusion, telemonitoring represents a powerful instrument for strengthening CKD self-management, but its real-world effectiveness depends on human-centered system design, continuous professional support, and tailored strategies to sustain patient adherence over time.